Articulation between the plastic arts and creative writing in vulnerable children: Red de Escritores de Medellín Project - Álvarez Galeano, Manuel Felipe (Revista Ecos de la Academia, 2024)
The investigation is presented, based on research on creative writing, based on reflections and conclusions arising from the axis of interdisciplinarity as a method of incentive and stimulation of communication skills (reading, writing, listening and speaking), during the Red de Escritores Ciudad de Medellín program. In this dialogue, dynamic strategies of approach are projected in these groups, in order to avoid revictimization, stigma, and propose ways of expression, strokes, creative writing and music, in discursive consonance with the realities, based on the contributions of Rodari, Cassany and others, based on various programs with support from the public sector, in settings such as prisons, educational units, foundations and cultural centers. Likewise, through these considerations, critical thinking is stimulated as a dynamic of daily questioning that tends towards an articulation between self-knowledge and the self-worth of individuals as subjects of rights.